PENGARUH PENGGUNAAN MEDIA KOMIK TERHADAP HASIL BELAJAR SISWA KELAS X SMA NEGERI 3 PONTIANAK PADA MATERI LARUTAN ELEKTROLIT DAN NONELEKTROLIT - Enawati, Eny; Sari, Hilma (Jurnal Pendidikan Matematika dan IPA, 2010)
The purposes of the research is to know the effect using media of comic toward student achievement learning in class X SMA Negeri 3 Pontianak for electrolit solution and non electrolit solution. The research uses experiment method and design research is Pretest Posttest Control Group Design. The subject research are student calss XE and XF, using purposive sampling to take the sample. The technique is used to gather the data is student achievement. Based on the data analisis using U-Mann Whitney test, 5 % level signification is found that Z count=-5,56 < Z tabel -1,96, there is the difference students learning achievement between using comic media and praktikum metod. There are 96,97 % student get higger learning achievement and get the KKM. The Effect size is 1,82, means learning using comic media give big effect 46,56 % towards the higger student achievement student class X SMA Negeri 3 Pontianak. The respon 30 students class XE towards learning electrolit solution and non electrolit solution using media of comic is 95,87 %. This is shows that learning using comic media is effective to teach electrolit solution and non electrolit solution in class X SMA Negeri 3 Pontianak. Keywords : electrolit solution and non electrolit solution, comic media, praktikum